2012
DOI: 10.1007/s10086-012-1311-5
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic and bending properties in Pinus elliottii beams obtained from trees of different ages

Abstract: In contrast to wood from native forests, the lumber harvested from planted forests is primarily composed of boards from younger trees. Given the possibility of using wave propagation methods to classify wood for structural purposes, it is important to evaluate if the ultrasonic parameters tend to vary with the age of the tree in a similar manner as static bending parameters. Experiments were conducted using structural beams taken from Pinus elliottii trees that were 8, 9, 13, 15, 22 and 23 years old. The beams… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…149 Gonçalves et al reported that the rate of acoustic velocity increase with age for Pinus elliottii was highest in younger trees. 147 …”
Section: Additional Factors Affecting Acoustic Velocity In Tree Stemsmentioning
confidence: 99%
“…149 Gonçalves et al reported that the rate of acoustic velocity increase with age for Pinus elliottii was highest in younger trees. 147 …”
Section: Additional Factors Affecting Acoustic Velocity In Tree Stemsmentioning
confidence: 99%
“…According to Baar et al [42] positive effects of density on wave velocity mostly abolished by some factors such as rigidity, macrostructure and micro-structure, chemical content of wood and others. Besides, age of tree assumed as another factor that affects the wave velocity [49]. Table 2 shows the calculated shear wave velocity through LR, LT, and RT planes.…”
Section: Resultsmentioning
confidence: 99%
“…An acoustic method has often been used for determining the wood quality of standing trees and logs; it could also be used for standing urban trees [31][32][33]. Moreover, earlier studies [34] showed a good correlation (R 2 = 0.63 to 0.91) between stress wave speed and the dynamic modulus of elasticity (MOE) of standing trees.…”
Section: Introductionmentioning
confidence: 99%